The racial politics of division : interethnic struggles for legitimacy in multicultural Miami - Gosin, Monika (Ithaca [New York] : Cornell University Press, 2019)
"Focusing on interminority tensions between African Americans, white Cubans, and Afro-Cubans in Miami when national trends toward majority-minority spaces had just begun to emerge, The Racial Politics of Division exposes the roots of interethnic conflict and their connection to the race-making practices of the Anglo elite, adding dimension to modern debates about race, blackness, immigration, and interethnic relations in multicultural America"--
Race making : Miami and the nation -- Marielitos, the criminalization of blackness, and constructions of worthy citizenship -- And justice for all? Immigration and African American solidarity -- Framing the Balsero Crisis : the racial and moral politics of suffering -- Afro-Cuban encounters at the intersections of blackness and latinidad.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 16, 2019).
JSTOR
Keywords: Miami (Fla.) -- Ethnic relations; Miami (Fla.) -- Race relations; Minorities -- Florida -- Miami -- Social conditions; Ethnic conflict -- Florida -- Miami; Minorités -- Floride -- Miami -- Conditions sociales; Conflits ethniques -- Floride -- Miami; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Ethnic conflict; Ethnic relations; Minorities -- Social conditions; Race relations; Florida -- Miami